Effect of digital brand experience on luxury fashion brand authenticity, attachment and loyalty - Fan-Lu Lin; Te-Hsing Ku (South African Journal of Business Management, 2023)
Purpose: The visual storytelling feature of Instagram provides luxury fashion brands with an appropriate platform to enhance their online presence and identity to build a greater connection with their audiences. This paper aims to examine how digital brand experiences on social media influence perceptions of brand authenticity, attachment and loyalty for luxury fashion brands.